Women on the Frontline - Johnson, Professor Chris. author. aut Link
XVIII, 197 p.
Keywords: Women's lives in southern Africa have undergone immense changes. War and economic hardship have separated families, education and outside influences have changed ideas about family life. This book records some of the stories of the women of the area and the changing world in which they live.